Alloy design for high-entropy alloys based on Pettifor map for binary compounds with 1:1 stoichiometry. (November 2015) - Takeuchi, A.; Amiya, K.; Wada, T.; Yubuta, K.
Abstract: Pettifor map for binary compounds with 1:1 stoichiometry was utilized as an alloy design for high-entropy alloys (HEAs) with exact or near equi-atomicity in multicomponent systems. Experiments started with selecting GuGd binary compound with CsCl structure from Pettifor map, followed by its extensions by selecting the binary compounds with the same CsCl structure to CuDyGdTbY equi-atomic quinary alloy and to Cu4 GdTbDyY and Ag4 GdTbDyY quinary alloys and Cu2 Ag2 GdTbDyY senary alloy in sequence. X-ray diffraction revealed that CuDyGdTbY alloy was formed into a HEA with mixture of bcc, fcc and hcp structures, whereas the Cu2 Ag2 GdTbDyY HEA was a single CsCl phase. The results suggest a potential of Pettifor map for the development of HEAs by utilizing its information of crystallographic structures. The further analysis was performed for composition diagrams of multicomponent systems corresponding to simplices in a high dimensional space. The present results revealed that a strategy of equi-mole of compounds instead of conventional equi-atomicity also works for the development of HEAs. Highlights: Pettifor Map was used for the development of high-entropy alloys. High-entropy alloys with CsCl structure were designed efficiently. Features of high-entropy alloys were demonstrated in composition diagrams. A new strategy based on equi-mole of compounds was adopted to high-entropy alloys. Paradigm shift in alloying high-entropy alloys has been achieved by Pettifor Map.